Identification and functional characterization of the German cockroach, Blattella germanica, short interspersed nuclear elements - Firsov, Sergei Yu.; Kosherova, Karina A.; Mukha, Dmitry V. (PLOS ONE, 2022)
In recent decades, experimental data has accumulated indicating that short interspersed nuclear elements (SINEs) can play a significant functional role in the regulation of gene expression in the host genome. In addition, molecular markers based on SINE insertion polymorphisms have been developed and are widely used for genetic differentiation of populations of eukaryotic organisms. Using routine bioinformatics analysis and publicly available genomic DNA and small RNA-seq data, we first described nine SINEs in the genome of the German cockroach, Blattella germanica. All described SINEs have tRNA promoters, and the start of their transcription begins 11 bp upstream of an “A” box of these promoters. The number of copies of the described SINEs in the B. germanica genome ranges from several copies to more than a thousand copies in a SINE-specific manner. Some of the described SINEs and their degenerate copies can be localized both in the introns of genes and loci known as piRNA clusters. piRNAs originating from piRNA clusters are shown to be mapped to seven of the nine types of SINEs described, including copies of SINEs localized in gene introns. We speculate that SINEs, localized in the introns of certain genes, may regulate the level of expression of these genes by a PIWI-related molecular mechanism.